Dynamics of twin boundaries in ferromagnetic shape memory alloys. (November 2014) - Faran, E.; Shilo, D.
Abstract : Combined experimental and theoretical investigation of discrete twin boundary motion in ferromagnetic shape memory alloys 10M NiMnGa is presented. Motion of individual boundaries is studied through mechanical tests and pulsed magnetic field experiments. Analysis of the experimental results leads to identification of two intrinsic energy barriers that dominate twinning kinetics and possible mechanism for overcoming these barriers. At low velocities, the twinning stress property is dictated by a long range (micrometre scale) periodic potential. At higher rates, a short range (nanometre scale) potential, which is related to the periodicity of the lattice, is responsible for the transition in kinetic behaviour from slower thermally activated to faster athermal motion. These observations enable formulation of different kinetic relations that are valid at different ranges of the driving force. The derived relations show a very good fit to the experimental results, allowing quantitative extraction of fundamental nanoscale properties of the twin boundary.